Ultrafast erbium doped fiber lasers using 2D nanomaterial based saturable absorbers / Mahmoud Hazzaa Mohammed Ahmed - Mahmoud Hazzaa , Mohammed Ahmed (2018)
The importance of ultrafast fiber lasers technology in science and engineering continues to grow as their performance offers great advantages. Therefore, ultrafast erbium-doped fiber lasers (EDFLs) have been demonstrated in this thesis using various new two-dimensional (2D) nanomaterials as a mode-locker. Here, new 2D nanomaterials like graphene, molybdenum disulfide (MoS2) and black phosphorus were explored as saturable absorbers (SAs) device. These SAs were fabricated, characterized and integrated into various EDFL cavities for realizing ultrafast laser. At first, a simple and compact mode-locked EDFL was demonstrated using nonconductive graphite pencil-core based SA. Then, stretched pulse and soliton femtosecond pulse generation with graphene SA were obtained by manipulating cavity dispersion. With dispersion management, the net cavity total dispersion can be decreased to -0.028 ps2, where stable stretched pulse with pulse width of 750 fs can be generated at a repetition rate of 35.1 MHz. Also, by varying the net cavity dispersion to -0.3 ps2, anomalous dispersion cavity has been achieved to generate soliton mode-locked pulses train with a pulse width of 820 fs and repetition rate of 11.5 MHz. Next, a few-layer molybdenum disulfide (MoS2) based SA was developed by mechanically exfoliating the material using scotch tape. A self-started mode-locked soliton pulse was successfully generated at a central wavelength of 1598.94 with pulse width and repetition rate of 830 fs, and 17.1 MHz, respectively. After that, a free-standing few-layer MoS2 polymer composite was fabricated by liquid phase exfoliation of chemically pristine MoS2 crystals and use this to demonstrate a soliton mode-locked EDFLs. A stable soliton pulse started at a low threshold pump power of 25 mW and has shorter pulse duration of 630 fs. Furthermore, a dissipative soliton with square pulse train was obtained by using MoS2 in the ultra-long cavity. Finally, through mechanically exfoliating a black phosphorus (BP) crystal, the BP-SA was obtained. A small piece of the BP flakes was then integrated into an EDFL cavity to achieve a self-started soliton mode-locked pulse operation at 1560.7 nm with shorter pulse duration of 570 fs and high pulse energy of 0.74 nJ. Overall, the emerging 2D nanomaterials as SA in fiber lasers cavity designs could be leveraged to yield tangible benefits for ultrafast lasers technology and we place our results in the full-text publication of ongoing research. The developed lasers will find possible applications in high-speed telecommunications, environmental sensing, metrology and biomedical diagnostics.